Pursuing Harmony and Fulfilling Responsibility: A Qualitative Study of the Orientation to Happiness (OTH) in Chinese Culture - Rong Dong; Yunxi Wang; Chenguang Wei; Xiangling Hou; Kang Ju; Yiming Liang; Juzhe Xi (Behavioral Sciences, 2023)
Happiness is the ultimate life goal for most people, and the pursuit of happiness serves as the fundamental motivation driving human behavior. Orientation to Happiness (OTH) represents the aspect that individuals seek when making decisions or engaging in activities, including values, priorities, motivations, ideals, and goals. Nevertheless, existing research has predominantly approached OTH from an individualistic perspective, emphasizing an individual’s internal emotional state and personal goals, thereby neglecting the significant influence of a collectivist cultural background on the pursuit of happiness. To address this research gap, our study employs qualitative research methods, enabling us to delve deeply into the intricate interplay between cultural context, societal influences, and individual motivations that collectively shape OTH. Our research is dedicated to understanding the structure of OTH within the Chinese cultural context. Through semi-structured interviews with 26 Chinese adults and the utilization of an inductive style of thematic analysis, we have identified two core themes within the OTH of Chinese adults: Self-focused and Other-focused. Notably, the “Other-focused” theme emphasizes the pursuit of group harmony and the fulfillment of group responsibilities, highlighting the paramount role of “relationships” in the study of happiness within collectivist cultures. This insight forms a robust foundation for future research in this area.